Implementation of Problem-Based Learning Model on Quantitative Research Method Courses - Solihat, Ai Nur; Disman, Disman (Economic Education Analysis Journal, 2022)
This study aimed to describe the implementation of problem-based learning models in quantitative research method courses. The method used a descriptive survey with a saturated sampling technique that took the entire population as a sample in the study, totaling 96 students of the Department of Economics Education, Faculty of Teacher Training and Education, Siliwangi University. Data was collected by distributing questionnaires through Google Forms consisting of 25 statement items from 6 indicators, namely aspects of student interaction with lecturers, being able to motivate student learning, effective, efficient and creative thinking competence, good time management competence, good student learning outcomes, and the suitability of the learning model with the characteristics of the course. Data analysis was performed by using descriptive statistics. Based on the results of the research that had been done, information was obtained that the problem-based learning model was a learning model that could improve the experience of learning outcomes. Problem-based learning model could also foster learning motivation, build student competencies in effective, efficient and creative thinking, build good time management competencies, and could improve learning outcomes, and could be implemented in research method courses.